Pemanfaatan Data Sentinel-2 untuk Analisis Indeks Area Terbakar (Burned Area) - Rahmi, Khalifah Insan Nur; Febrianti, Nur (Masyarakat Ahli Penginderaan Jauh Indonesia (MAPIN) /Indonesian Society of Remote Sensing (ISRS), 2020)
The Use of Sentinel-2 Image to Analysis Burned Area Index Burned area mapping can be extracted from remote sensing imagery using burned area index. Various indices have been developed to identify burned areas including NBR, NBR2, MIRBI, and BAIS2. This study aims to determine the index that best distinguishes burning and non-burning areas in the detailed scale of small fires. Burned areas were identified from the delta index before and after the fire. Date of Sentinel-2 image before fires on May 1, 2019, after fires on September 8, 2019. The NBR index uses the comparison of SWIR and NIR band, the NBR2 and MIRBI indexes use the comparison of SWIRL and SWIRS band, while the BAIS2 index plays the red-edge spectral range, NIR, and SWIR. The result of the separability index analysis shows that the MIRBI index is good for distinguishing burned areas from bare land. The NBR index is good at distinguishing burned areas from vegetation and built-up land while the NBR2 index is good at distinguishing smoked burned areas from vegetation and built-up land.